Correlation of the triglyceride-glucose index with major adverse cardiovascular events in type 2 diabetes mellitus patients with acute myocardial infarction combined with HFpEF - Xiaodong Zhang; Xiaodong Zhang; Nan Niu; Shengqin Yu; Xinxin Zhang; Xuefu Chen; Ming Yu; Wenmiao Zhang; Ying Liu; Zhenwei Wang (Frontiers in Endocrinology)
AimsThis study was conducted to evaluate the correlation between triglyceride-glucose index (TyG) and major adverse cardiovascular events (MACE) in patients with type 2 diabetes mellitus (T2DM) and heart failure with preserved ejection fraction (HFpEF) after acute myocardial infarction (AMI).MethodsThis retrospective study at the First Affiliated Hospital of Dalian Medical University included 400 AMI patients with T2DM and HFpEF who underwent percutaneous coronary intervention (PCI) between 1 January 2018 and 1 January 2023. The study was conducted using univariate and multivariate Cox regression analyses, subgroup analyses, receiver operating characteristic (ROC) curves, and Kaplan–Meier survival curves to assess the correlation between the TyG index and MACE.ResultsMultivariate Cox regression analyses showed that in model 3 with variables fully adjusted, when TyG was used as a categorical variable, the risk of MACE in the TyG T2 and T3 groups was 1.622 times and 2.247 times higher than that in the T1 group, respectively (P < 0.05). When TyG was used as a continuous variable, the risk of MACE increased by 49.5% for every 1 unit increase in the TyG index (P < 0.001). In the subgroup analysis, elevated TyG index levels were consistently associated with an increased risk of MACE across multiple clinical subgroups (P < 0.05). ROC analysis showed that the TyG index significantly predicted the occurrence of MACE (AUC: 0.635, 95% CI: 0.580–0.691, P < 0.001), all-cause death (AUC: 0.565, 95% CI: 0.508–0.622, P = 0.027), non-fatal myocardial infarction (AUC: 0.617, 95% CI: 0.542–0.693, P = 0.004), and unplanned revascularization (AUC: 0.644, 95% CI: 0.578–0.710, P < 0.001). The Kaplan–Meier survival curves revealed statistically significant differences in survival probabilities for the occurrence of MACE, all-cause death, non-fatal myocardial infarction, and unplanned revascularization across the three TyG index groups as the follow-up period progressed (P < 0.05).ConclusionsThe TyG index was independently associated with MACE in T2DM patients with AMI combined with HFpEF.